Protein Science Encyclopedia 2008
DOI: 10.1002/9783527610754.sa07
|View full text |Cite
|
Sign up to set email alerts
|

Studying Protein Folding and Aggregation by Laser Light Scattering

Abstract: Originally published in: Protein Folding Handbook. Part I. Edited by Johannes Buchner and Thomas Kiefhaber. Copyright © 2005 Wiley‐VCH Verlag GmbH & Co. KGaA Weinheim. Print ISBN: 3‐527‐30784‐2 The sections in this article are Introduction Basic Principles of Laser Light Scattering Light Scattering by Macromolecular Solutions Molecular Parameters Obtained from Static Light S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 76 publications
0
8
0
Order By: Relevance
“…It has been well established that the hydrodynamic dimension of a protein increases upon denaturation, and thus DLS can be used to characterize protein-folding states. 10 In this study, we demonstrated that the r H value measured by DLS provides enough resolution to capture multiple intermediate states of BSA upon denaturation. There are several advantages of using DLS to monitor protein-folding states over spectroscopy-based methods such as CD and fluorescence.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…It has been well established that the hydrodynamic dimension of a protein increases upon denaturation, and thus DLS can be used to characterize protein-folding states. 10 In this study, we demonstrated that the r H value measured by DLS provides enough resolution to capture multiple intermediate states of BSA upon denaturation. There are several advantages of using DLS to monitor protein-folding states over spectroscopy-based methods such as CD and fluorescence.…”
Section: Discussionmentioning
confidence: 70%
“…DLS is well known for the quick, nonperturbing nature of measurement, and for the ability to measure a wide spectrum of particles ranging from 1 nm to 5 μm. In addition, as the hydrodynamic dimension of a protein increases upon denaturation, DLS has also been successfully applied in studying protein‐folding states …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the essential role of ATP in the peroxidase activity, we evaluated changes in the structure of 2-Cys Prx brought about by the concerted action of the nucleotide and the bivalent cation. To accurately determine the molecular mass of our 2-Cys Prx preparations, static light-scattering measurements were performed, because this spectroscopic technique allows direct estimation of the species in solution [23]. In the absence of perturbants, the predominant form of After the addition of EGTA to a final concentration of 5 mM, the protein solution was further incubated for 5 min and the peroxidase activity was assayed as in (A).…”
Section: The Interaction With Atp Modifies Structural Features Of 2-cmentioning
confidence: 99%
“…A key motivation is that many proteins are marginally stable and only fold in the presence of their ligands or binding partners, opening new regulatory possibilities (1,2). An important reason for recent progress is the growing availability of methods that provide structural information on these conformationally heterogeneous systems, such as NMR (3), scattering methods (4,5), and single-molecule FRET (6)(7)(8). Although NMR provides mostly local details, small-angle X-ray scattering (SAXS), dynamic light scattering (DLS), and single-molecule FRET provide overall hydrodynamic or long-range distance information.…”
mentioning
confidence: 99%